2023
DOI: 10.1021/acsami.3c10011
|View full text |Cite
|
Sign up to set email alerts
|

Phase Interface Regulating on Amorphous/Crystalline Bismuth Catalyst for Boosted Electrocatalytic CO2 Reduction to Formate

Chenchen Qin,
Li Xu,
Jian Zhang
et al.

Abstract: Electroreduction of carbon dioxide into readily collectable and highvalue carbon-based fuels is greatly significant to overcome the energy and environmental crises yet challenging in the development of robust and highly efficient electrocatalysts. Herein, a bismuth (Bi) heterophase electrode with enriched amorphous/crystalline interfaces was fabricated via cathodically in situ transformation of Bi-based metal-phenolic complexes (Bi-tannic acid, Bi-TA). Compared with amorphous or crystalline Bi catalyst, the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…[22a,23] Compared with c-CdS/CP (263.4 mV dec À 1 ) and c-CdS/c-Cd(OH) 2 @CP (377.6 mV dec À 1 ) electrodes, the c-CdS/a-Cd(OH) 2 /CP electrode exhibited the smallest Tafel slope (114.3 mV dec À 1 ), demonstrating the exceptional electrochemical CO 2 reduction activity, consistent with its electrocatalytic performance in Figure 2. According to the previous study, [14] it has been demonstrated that the introduction of the amorphous domain in the electrode could efficiently regulate the interaction between active sites and reaction intermediates, thereby affecting the electrochemical activity. In this study, we carried out the in-situ attenuated total reflection infrared (ATR-IR) spectroscopy to study the surface-adsorbed reaction intermediates at different potentials.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[22a,23] Compared with c-CdS/CP (263.4 mV dec À 1 ) and c-CdS/c-Cd(OH) 2 @CP (377.6 mV dec À 1 ) electrodes, the c-CdS/a-Cd(OH) 2 /CP electrode exhibited the smallest Tafel slope (114.3 mV dec À 1 ), demonstrating the exceptional electrochemical CO 2 reduction activity, consistent with its electrocatalytic performance in Figure 2. According to the previous study, [14] it has been demonstrated that the introduction of the amorphous domain in the electrode could efficiently regulate the interaction between active sites and reaction intermediates, thereby affecting the electrochemical activity. In this study, we carried out the in-situ attenuated total reflection infrared (ATR-IR) spectroscopy to study the surface-adsorbed reaction intermediates at different potentials.…”
Section: Resultsmentioning
confidence: 93%
“…[13] Furthermore, the interface between amorphous and crystalline domains could offer more activated atoms to promote CO 2 adsorption and decrease the energy barrier of the rate-determining step, thereby improving the electrochemical efficiency. [14] Recently, Wang et al fabricated a Bi electrode with abundant amorphous and crystalline interfaces, which could efficiently catalyze CO 2 to formate with high selectivity of > 90 % in a wide potential range, obviously superior to its crystalline counterpart. Inspired by these, it is reasonable to assume that the electrochemical activity of CdSbased electrocatalysts could be enhanced by creating a composite structure of amorphous and crystalline domains.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the In sites were revealed as the active sites for CO 2 adsorption and conversion on the models of In and In 2 O 3 (Figure S22). To understand electron density and atomic orbital contributions from both In atoms and O atoms and elucidate the strength of interaction between the catalyst and intermediates, a projected density of states (PDOS) analysis was performed on catalysts with adsorbed *HCOO intermediates. , The PDOS near Fermi level ( E f ) for In/In 2 O 3– x exhibited dominant p-orbital electron states with significantly higher electronic densities than s- and d-orbitals (Figure S23), indicating a stronger interaction toward intermediates. Upon adsorption of *HCOO intermediates, harmonic overlap between p orbitals of the O atom in intermediates and p orbitals of the In atom was observed (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The RDS observed on Bi@Bi 2 O 2 CO 3 required more energy input than that of Bi@Bi 2 MoO 6 (0.80 eV vs 0.52 eV). The p-projected density of states (p-PDOS) analysis was performed on catalysts with adsorbed intermediates to elucidate the strength of interaction between the catalyst and intermediates. , The orbital overlap area between Bi p orbitals of Bi@Bi 2 MoO 6 and O p orbitals of intermediate *OCHO is larger compared to that of Bi@Bi 2 O 2 CO 3 , indicating a higher propensity for stabilizing *OCHO intermediates on Bi@Bi 2 MoO 6 (Figure e). Therefore, the anion exchange of CO 3 2– (replacing MoO 4 2– ) into the [BiO] + interlayer would hinder the generation of *OCHO, leading to decreased catalyst activity.…”
Section: Results and Discussionmentioning
confidence: 99%